Evaluation of in vitro anthelminthic activity of indian acalypha (Acalypha indica) root extract against l3 stage strongyle larvae in sheep - Priyangah, Vasu (2019)
Gastrointestinal nematode (GIN) infection has been identified as the second most important cause of small ruminant mortality and morbidity in Malaysia. To control GIN infection, commercial anthehninthic drugs (AHO) are used. However, continuous unscrupulous usage of AHO has inevitably resulted in rampant anthelminthic resistance in numerous small ruminant farms in Malaysia. Hence, ethnoveterinary medicine is actively explored to find an alternative to commercial AHD. This study aims to evaluate the anthehninthic activity of Acalypha indica, a common tropical weed, against L3 strongyle larvae in sheep. A total of 300 L3 larvae were assigned to 5 experimental groups (40, 50 and 60 mg/ml Indian Acalypha Root Methanolic Extract (IARME), ivermectin and distilled water. The average percentage of L3 larvae mortality were recorded at time 0, 10 and 30 minutes, 1, 2, 3, 4 and 24 hours. The results showed that 60 mg/ml IARME displayed the highest percentage of L3 mortality against time, whereby 100% mortality was achieved in 3 hours. IARME exhibited significant anthelminthic activity in a dose dependent manner when compared to ivermectin. In conclusi on, this study showed that Acalypha indica roots has the potential to be used as an alternative to control GIN in sheep.